EKSPLORASI SIMBOLIS DAN ESTETIKA AKSESORIS PAKAIAN ADAT SUKU BATULOLONG KECAMATAN ALOR SELATAN - Asriyanti Karim; Ayu Maubuthy; Asrina Takalapeta; Asarina Alomalai; Belandina Edelweis Atalo; Beci Oko; Halena Muna Bekata; Petrus Mau Tellu Dony (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to examine the symbolic meaning and aesthetics of accessories on traditional clothing of the Maleipea Village community, South Alor Sub-district, Alor Regency. Traditional clothing accessories in this village not only function as a fashion complement, but also contain cultural values that represent the identity, social status, and spirituality of the local community. This research uses a qualitative method. With an ethnographic approach, this research involved data collection techniques, namely participant observation and in-depth interviews to explore a deep understanding of the role of accessories in daily life and traditional ceremonies. The data analysis technique used, namely qualitative descriptive analysis. The results showed that each element of accessories, from materials to colours, has its own symbolism that reflects the community's harmonious relationship with nature as well as traditional values that have been passed down from generation to generation. In addition, the aesthetics of the accessories are reflected in the use of natural materials such as native rattan (tibu), wire, red cloth, chicken feathers, forest deli fruit, yarn, and fan rope (van belt) arranged with traditional craft techniques. This research makes an important contribution to the preservation of local culture as well as a reference in the development of Nusantara cultural studies.